Herbigation in a Vineyard: Persistence of Four Pre-emergence Herbicides in a Sandy Loam Soil - Fourie, J.C. (South African Journal of Enology and Viticulture, 2017)
The persistence of simazine, oxadiazon, napropamide and oryzalin in a sandy loam soil was monitored over a period of 60 days by means of a bio-assay. Avena saliva L (oat) [oxadiazon and oryzalin] and Hordeum vulgare L. (barley) [simazine and napropamide] were used in the bio-assay. Sixty days after application 12%, 16%, 38% and 76% of simazine, oxadiazon, oryzalin and napropamide, respectively, initially present, were detected in the 0-300 mm soil layer, the latter herbicide being the most persistent. Migration, to a greater or lesser extent, could be detected in the case of simazine, oxadiazon and napropamide. Oryzalin was seemingly resistant to leaching. A 20 mm herbigation seemed optimal for oryzalin and napropamide. In the case of oxadiazon and simazine, however, it is suggested that the herbigation volume should be reduced to 15 mm. It was confirmed that the use of wettable powders for herbigation should be avoided and solutions should rather be used. The criteria established for herbigation on a sandy loam soil could be used as a guideline for medium-textured soils.